Jennifer's Stories - Ogbu, Nneoma Jennifer (Rasmed Publications Ltd, 2001)
This is a collection of stories such as The Victory of Ikem and the evil of disobedience.
Keywords: Collection of Stories; Juvenile Fiction; Realistic